Telomere length‐related gene ACYP2 polymorphism is associated with the risk of HAPE in Chinese Han population. (September 2016) - He, Yongjun; Zhang, Xiyang; Li, Xun; Du, Jieli; He, Xue; Zhang, Zhiying; Zhang, Yuan; Kang, Longli; Jin, Tianbo; Yuan, Dongya
Abstract: Background: High altitude pulmonary edema (HAPE) is a type of pneumonedema that mostly occurs under conditions such as high altitude, rapid ascent and hypoxia, amongst others. The ACYP2 polymorphism is suggested to be associated with mean telomere length, and telomere length is significantly longer at a moderate attitude than at sea‐level or at simulated high attitude. The present study aimed to determine whethher there is any association between ACYP2 polymorphism and the risk of HAPE. Methods: A total of 265 patients and 303 healthy controls were enrolled in our case‐control study. Six SNPs were selected and genotyped using the Sequenom MassARRAY method. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated by unconditional logistic regression with adjustment for gender and age. Results: Using chi‐squared tests, we found that the minor allele G of rs11896604 is significantly associated with a decreased risk of HAPE [odds ratio (OR) = 0.87, 95% confidence interval (CI) = 0.65–1.16, p  = 0.048]. We also found that the 'A/A' genotype of rs12615793 is associated with a decreased risk of HAPE based on the recessive model (OR =0.28; 95% CI = 0.09–0.88; p  = 0.017). Additionally, the 'G/G' genotype of rs11896604 was found to be associated with a decreased risk of HAPE based on the codominant model (OR =0.26; 95% CI = 0.08–0.79; p  = 0.025) and recessive model (OR =0.25; 95% CI = 0.08–0.77; p  = 0.007). However, only rs11896604 remained significant after Bonferroni correction ( p  < 0.0083). Conclusions: The present study found that the ACYP2 gene polymorphism significantly decreased the risk of HAPE. Copyright © 2016 John Wiley & Sons, Ltd. Copyright © 2016 John Wiley & Sons, Ltd.